History of law in Latin America. Transition to the Republic - Vásquez Pérez, Albert (2024)
This article provides a comprehensive analysis of the legal evolution during the transition from colonies to independent republics in the region. It delves into the challenges and conflicts inherent to this process, including the struggle for autonomy, the consolidation of political and organizational systems, along with the rearrangement of legal structures left by colonialism. Furthermore, it highlights crucial moments such as the emergence of new nations and the consolidation of institutions that improved the application of law in these societies. This study offers a solid foundation for understanding the current state of law in Latin America, anchored in the history of law during the transition to the Republic. It also provides relevant reflections on the future of the legal system in the region, rooted in the historical lessons learned during this critical period of political and legal transformation.